Research-practice partnerships "On the Ground": Exploring partnership work in urban schools under pressure to improve. (September 2021) - Weddle, Hayley; Lockton, Marie; Datnow, Amanda
Highlights: Qualitative research methods strengthened research-practice partnership (RPP) work over time. Interviews and observations served as a vehicle for teachers to actively engage in the RPP. Accountability pressures and conflicting reforms mediated educators' engagement in RPP work. Abstract: Research-practice partnerships (RPPs) are intended to engage researchers and practitioners as equal partners to address urgent problems of practice. While this goal is clear, more remains to be learned about RPP efforts "on the ground." This paper is written from our vantage point as qualitative researchers on a project that involved a multi-year partnership between university researchers and four urban schools under pressure to improve student achievement. We examine the contextual factors shaping RPP work in these schools, as well as the role of qualitative research in supporting the partnership. Findings indicate that strong accountability pressures mediated how teachers viewed improvement efforts, causing them to be initially wary of data-focused RPP activities. Navigating multiple concurrent reform efforts as well as persistent teacher turnover also impacted the RPP. Importantly, qualitative research methods helped to strengthen RPP work over time and served as a main vehicle by which teachers engaged as active participants in the partnership. Implications from this study are presented to inform future development of meaningful and reciprocal partnerships.